Theoretical Study of Alkylation of 4-amino-1,2,4-Triazol in Presence of Aluminium Chloride - KPOTIN, ASSONGBA GASTON; KUEVI, URBAIN AMAH; KPOTA HOUNGUE, MAHOUGBE TATA ALICE; ATOHOUN, YACOLÈ GUY SYLVAIN; MENSAH, JEAN-BAPTISTE (My University, 2017)
The theoretical study of alkylation of 4-amino-1,2,4-triazol (C2N4H4) in the presence of aluminum chloride (AlCl3) was carried out by quantum chemical methods HF and DFT, in Lanl2Dz basis set. The results show that N-alkyl product is favorable thermodynamically. And the aluminum chloride decreases the activation energy.
Keywords: Alkylation; 4-amino-1; 2; 4-triazol; Aluminum chloride; HF; DFT; Lanl2DZ